Ejercicio de la acción de repetición en las fuerzas militares y de policía en los grados de generales de la república (2017)
The Action for Repetition is defined as: the mechanism that the Administration has for its Public Officials, to restore the money that the State has paid as compensation, for their guilty or willful misconduct when making decisions, and for the which the Colombian State has been condemned; convictions that have been increasing, and which are reflected in the numerous judgments issued against the Nation, and which are generated in large part by the Public Force( Military and Police); who at the head of the high command, are in charge of the responsibility of their agents, and of their actions; Superiors who are called to respond even with their own patrimony, when The State has paid the sentences for the damages caused by these officials.